The role of nutrition in COVID-19 pandemic - Lestari Octavia; Johan Harlan (International Journal of Public Health Science (IJPHS), 2021)
In the ongoing coronavirus disease 19 (COVID-19) pandemic, the most vulnerable groups are those with pre-existing health problems and the elderly due to their reduced immune system to prevent infection. Nutrition plays a significant role in maintaining the immune system to prevent pathogen manifestation. This review aimed to identify and discuss the role of nutrients in COVID-19 in developing immunity. Studies included in this review were obtained from articles published in reputable journals accessed from the National Center for Biotechnology Information (NCBI) website, leading search engine, in a retrospective timeframe from January 1 to May 2, 2020, using specified keywords. The search resulted in seven articles relevant to the objective of the review. They highlighted the role of nutrients, namely the deficiency of essential nutrients that might exacerbate the health status. The consumption of certain nutrients, micronutrient and omega-3 might be tolerated up to the upper level of recommended dietary allowance (RDA) to benefit the health status. This review can assist in providing the prevention and mitigation approach to improve immunity amid the COVID-19 pandemic. The government should expand the continuous delivery of messages regarding the benefit of appropriate nutrients in maintaining health and immune system. Furthermore, the current condition gives the best opportunity to educate the community on a healthy and balanced diet for daily life.